PENERAPAN MODEL KOOPERATIF STAD BERBANTUAN MEDIA ULAR BERBUNYI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV DI SD SIDOMUKTI 01 - Ronald Oktavianus; F.Shoufika Hilyana; Sekar Dwi Ardianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was conducted because of the low learning outcomes of fourth grade students of SD Sidomukti 01 in the science content as indicated by the initial data acquisition. This study used a qualitative experimental method. The location of this research was at SD Sidomukti 01, Margoyoso District, Pati Regency. The sample used was 12 fourth grade students. The implementation of the Pancasila Student Profile Strengthening Project in fifth grade of SD N Sidomulyo was carried out through mustard greens planting activities. The data collection methods used in this study included observation, interviews, and documentation. As well as using data analysis techniques for validity tests, data normality tests, t-tests and n-gain tests. The results of the study showed the results of the paired sample t-test, namely there was a difference in the average pretest and posttest values, namely 51.9167 for the pretest value and 80.0833 for the posttest results. In addition, the Sig. (2-tailed) value was 0.000 <0.05, so Ho was rejected and Ha was accepted. So it can be interpreted that there is a difference in the average score of the pretest and posttest. The N-gain test shows an N-gain value of 0.7857, which means that the criteria for improving learning outcomes have increased with moderate criteria.